Artificial Red Blood Cells Constructed by Replacing Heme with Perfluorodecalin for Hypoxia‐Induced Radioresistance. Issue 6 (27th March 2019) - Yu, Peng; Han, Xiaoxue; Yin, Lining; Hui, Kangyu; Guo, Yunfei; Yuan, Ahu; Hu, Yiqiao; Wu, Jinhui
Abstract: Radioresistance, a serious problem during radiotherapy (RT) caused by hypoxia, results in tumor relapse. Hemoglobin‐based oxygen carriers (HBOCs) which can deliver oxygen, offer a promising option to cancer patients with radioresistance. However, the potential autoxidative cytotoxicity and renal toxicity of heme in hemoglobin (Hb) hamper their clinical application. Thus, here, a nano red blood cell (nnRBC) is fabricated that replaces heme with perfluorodecalin (FDC), a hydrophobic, high oxygen carrying fluorocarbon, and coated with membranes of RBCs. For the first time, nnRBCs provide a new method for the delivery of FDC since it cannot be emulsified by any FDA approved emulsifiers. nnRBCs encapsulate FDC with 8000% (w/w) drug loading efficiency and show superior storage stability within seven days. After intravenous delivery, nnRBCs reverse tumor hypoxia effectively compared with RT treatment alone. Of note, the components of nnRBCs are all from organisms or safe substances that have been verified by human testing, which gives nnRBCs great potential to rapidly enter into clinical trials. Abstract : Radioresistance usually causes tumor progression and metastases in hypoxic tumors . Here, a novel artificial blood cell (nnRBC) constructed by a simple "heme replacement" method exhibits high oxygen‐loading, long‐lasting stability, and low renal toxicity. It significantly enhances the efficacy of radiotherapy and may have promising applications as an artificial blood substitute.